Epidemiology and Outcomes of Acute Respiratory Distress Syndrome Following Isolated Severe Traumatic Brain Injury. (January 2022) - Komisarow, Jordan M.; Chen, Fangyu; Vavilala, Monica S.; Laskowitz, Daniel; James, Michael L.; Krishnamoorthy, Vijay
Patients with traumatic brain injury (TBI) are at risk for extra-cranial complications, such as the acute respiratory distress syndrome (ARDS). We conducted an analysis of risk factors, mortality, and healthcare utilization associated with ARDS following isolated severe TBI. The National Trauma Data Bank (NTDB) dataset files from 2007-2014 were used to identify adult patients who suffered isolated [other body region-specific Abbreviated Injury Scale (AIS) < 3] severe TBI [admission total Glasgow Coma Scale (GCS) from 3 to 8 and head region-specific AIS >3]. In-hospital mortality was compared between patients who developed ARDS and those who did not. Utilization of healthcare resources (ICU length of stay, hospital length of stay, duration of mechanical ventilation, and frequency of tracheostomy and gastrostomy tube placement) was also examined. This retrospective cohort study included 38, 213 patients with an overall ARDS occurrence of 7.5%. Younger age, admission tachycardia, pre-existing vascular and respiratory diseases, and pneumonia were associated with the development of ARDS. Compared to patients without ARDS, patients that developed ARDS experienced increased in-hospital mortality (OR 1.13, 95% CI 1.01-1.26), length of stay (p = <0.001), duration of mechanical ventilation (p = < 0.001), and placement of tracheostomy (OR 2.70, 95% CI 2.34-3.13) and gastrostomy (OR 2.42, 95% CI 2.06-2.84). After isolated severe TBI, ARDS is associated with increased mortality and healthcare utilization. Future studies should focus on both prevention and management strategies specific to TBI-associated ARDS.